ISB watermarking embedding: block based model - Zeki, Akram M.; Abdul Manaf, Azizah (Asian Network for Scientific Information, 2011)
Many watermarking methods have been developed with different methodological complexity levels. Each of these methods tries to reduce exposure in different attack. In this study, the ISB watermarking method was implemented based on average of block of pixels together in order to improve the watermarking method to be more resistant against attacks than a single pixel. The results show that the quality of the images is suitable for the application of the proposed method, based on any size of block. In additional to that the robustness has been improved by increasing the size of the block for all the attacks, including the geometric transform attacks, although they were not improved when the method was applied based on only one pixel.